Shaping the identity of novice academics: strategies for support professional development - Idoia Fernández-Fernández; Clemente Lobato Fraile (Forum Neue Medien in der Lehre Austria, 2016)
Studies on professional development and the construction of teaching identities in Higher Education point to the need to review the induction process for novice academics and to establish programmes that support their inclusion in the university. This article analyses such a programme, focusing on strategies used to construct an academic teaching identity. The results allowed participants to feel included, to construct rational guidelines for teaching, and to construct clear scenarios for understanding their tasks within the institution. However, the results also highlight the need to integrate the research side into the programme, thus helping them to construct a global academic identity that integrates the teaching self and the investigating self. 30.09.2016 | Idoia Fernández-Fernandez & Clemente Lobato Fraile (Bilbao)